Experiences in the reconciliation process: Period 1996-2004 - Golubović Nada (Temida, 2004)
The war in Bosnia and Herzegovina has left behind uninhabited, destroyed burnt down and devastated villages. The cities’ demographic picture has been changed, as well as the ethnic and social structure. That is why we have been conducting our activities in the community reconciliation process in rural and urban areas, applying different methods of work. Our activities were aimed at all national and social groups. Our association’s target group is women. With our activities, we are trying to raise public awareness about the women’s issues and to find solutions to those problems. We have worked on key problems that arose as a consequence of war experiences, which were brought forward by the women. We are trying to achieve an insight into the problems that are common to the women from different social and ethnic groups and, by attempting to solve them; we work on conflict resolution and transformation.